2014
DOI: 10.3109/09638288.2014.911969
|View full text |Cite
|
Sign up to set email alerts
|

Fast gait speed and self-perceived balance as valid predictors and discriminators of independent community walking at 6 months post-stroke – a preliminary study

Abstract: Fast speed and self-perceived balance appear to be important characteristics of ICW at 6 months and may be useful early predictors of the potential for patients to achieve this. Further research is needed to ensure the precision of these functional cut-offs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Community ambulation levels This method was presented by Rosa et al [20] concerning the difficulties experienced in outdoor ambulation after stroke, which is a self-reporting questionnaire that allows the participants to describe their level of community ambulation ability. The questionnaire has 5 dimensions as follows [20]: (1) have no difficulty in walking in the community and do not require physical assistance or supervision; (2) mild difficulty in walking in the community, requiring supervision to walk far away from home; (3) moderate difficulty, needing supervision to walk near and far away from the home; (4) severe difficulty in walking in the community, always requiring physical assistance from another person; and (5) does not walk outside of the home.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Community ambulation levels This method was presented by Rosa et al [20] concerning the difficulties experienced in outdoor ambulation after stroke, which is a self-reporting questionnaire that allows the participants to describe their level of community ambulation ability. The questionnaire has 5 dimensions as follows [20]: (1) have no difficulty in walking in the community and do not require physical assistance or supervision; (2) mild difficulty in walking in the community, requiring supervision to walk far away from home; (3) moderate difficulty, needing supervision to walk near and far away from the home; (4) severe difficulty in walking in the community, always requiring physical assistance from another person; and (5) does not walk outside of the home.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The questionnaire has 5 dimensions as follows [20]: (1) have no difficulty in walking in the community and do not require physical assistance or supervision; (2) mild difficulty in walking in the community, requiring supervision to walk far away from home; (3) moderate difficulty, needing supervision to walk near and far away from the home; (4) severe difficulty in walking in the community, always requiring physical assistance from another person; and (5) does not walk outside of the home. Subjects who responded to level 1 were divided up into "Independent Community Ambulation (ICA)".…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Previous studies have found that outcome measures such as lower-limb muscular strength, [1][2][3] balance, [4][5][6][7][8] walking speed, [9][10][11][12][13][14] and cognitive function 15,16) are related to walking independence in elderly persons and in patients with stroke disease. However, outcome measures related to walking independence in patients with medical diseases have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a majority report limitations even during the chronic phase of their recovery (Barclay et al, 2014;Rosa et al, 2014;van der Zee et al, 2013;Robinson et al, 2011b). Older adults with mobility limitations demonstrate a reduced frequency of community trips per day and have a tendency to avoid community environments (Lord et al, 2010;Shumway-Cook et al, 2005a;Shumway-Cook et al, 2002).…”
Section: Distancementioning
confidence: 99%
“…A number of factors within any of the ICF domains are associated with reduced ambulation activity and community ambulation after stroke (Rosa et al, 2014;Robinson et al, 2013;Rosenberg et al, 2013;Alzahrani et al, 2012;Danielsson et al, 2011;Robinson et al, 2011a;Robinson et al, 2011b;Fulk et al, 2010;Lord et al, 2004;Shumway-Cook et al, 2002). Yet few studies have prospectively investigated a combination of factors within multiple domains of the ICF on free-living ambulation outcomes across the subacute phase of stroke.…”
Section: Factors Affecting Ambulation After Strokementioning
confidence: 99%